1984
DOI: 10.1002/ijc.2910330513
|View full text |Cite
|
Sign up to set email alerts
|

Nyctohemeral changes in plasma prolactin levels and their relationship to breast cancer risk

Abstract: The amount of prolactin has been determined in serial blood samples taken over 24 h from 20 pre- and 9 postmenopausal women volunteers. All women had a large increase in prolactin at night (24.00 h-03.00 h). A much smaller rise in prolactin occurred in the evening (18.00 h-20.00 h) which was just significantly different (p less than 0.05) from levels found in the afternoon. Prolactin concentrations at any given time in the 29 women were linearly correlated with corresponding levels in either of the adjacent ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The current results support this conclusion, but some caution should be maintained because bioassays may provide a better measure of HPr than do current radioimmunoassay methods (Rose et al, 1987b). HPr declines with increasing parity (Yu et al, 1981;Wang et al, 1984), but the effect is small beyond three births (Wang et al, 1987), so the difference in parity between the Chinese and British women in the current study would not have been expected to have a large effect on HPr.…”
Section: Assaysmentioning
confidence: 61%
See 1 more Smart Citation
“…The current results support this conclusion, but some caution should be maintained because bioassays may provide a better measure of HPr than do current radioimmunoassay methods (Rose et al, 1987b). HPr declines with increasing parity (Yu et al, 1981;Wang et al, 1984), but the effect is small beyond three births (Wang et al, 1987), so the difference in parity between the Chinese and British women in the current study would not have been expected to have a large effect on HPr.…”
Section: Assaysmentioning
confidence: 61%
“…SHBG falls during the night (Moore & Bulbrook, 1988) but does not vary significantly between morning and early evening (Key et al, 1990). HPr is high during the night and falls after waking (Gray et al, 1981), but rises a little during the afternoon and early evening (Wang et al, 1984), so that the direction of any bias between countries in our results for HPr is not clear. In a study in Finland (which is much further north than China), Kauppila et al (1987) found that mean E2 and T concentrations in premenopausal women were 13% and 12% lower respectively during the darkest months (November to January) than during the lightest months (May to June), so it is possible that the Chinese samples in the current study are a slight underestimate of year-round E2 and T. Kauppila et al (1987) found that seasonal changes in mean SHBG and HPr concentrations were negligible.…”
Section: Assaysmentioning
confidence: 69%
“…Inconsistent findings in relation to female breast cancer risk (36-39) may be due to difficulties with sampling, owing to daily and monthly variations in prolactin levels (35,36,40). Serum prolactin levels are also considerably lower than breast fluid prolactin levels (41).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is interesting to note that serum prolactin levels are suppressed in young women in proportion to the number of children to which they have given birth [165]. There is also increasing evidence that estrogen receptor levels are inversely proportional to epidermal growth factor receptor levels [153].…”
Section: Reproductive Factorsmentioning
confidence: 97%